Trait anger, anger expression, coping strategies and self-esteem among elite taekwondo players - Atay, I. M.; Aydin, C.; Karatosun, H. (Medicina dello Sport, 2013)
Aim. Trait anger, anger expression styles, coping strategies and self-esteem levels of elite taekwondo players and swimmers of national teams were evaluated and compared. Methods. In the study, 30 elite swimmers and 30 elite taekwondo players who professionally participate in competitions for a minimum of 2 years were included. A control group (N.=30), matched with the study group in terms of age, gender and educational status who do not play sport regularly was also included in the study. Sociodemographic data form, Spielberger State-Trait Anger Expression Inventory, Ways of Coping Inventory, Rosenberg Self-Esteem Scale were administered to all participants. Results. In the comparison of the Stress-Coping Inventory between taekwondo players and the control group, taekwondo players were significantly found more reliant on positive reappraisal strategies in stressful situations than the control group and the scores for planned problem solving were also significantly higher in taekwondo players than in the control group. No significant difference was found between the scores of trait anger, anger-internal, anger-external and anger-control among all sporters and the control group. Self-esteem scores of taekwondo players were found to be significantly higher than swimmers. Conclusion. Taekwondo has positive effects on self-esteem compared to swimming, which is an individual sport. Taekwondo players were more organized with regard to problem solving strategies compared to persons who do not play sports, and taekwondo players were found to have more positive reappraisal strategies in stressful situations. Taekwondo, which is a martial art, contributes positively to the development of self-esteem and the ability to cope with problems.